Comparison of Toxoplasma gondii counts in chicken and duck brain samples sold at Keputran Market, Surabaya - Cahyani, Yuliana Dwi Kurnia; Lukiyono, Yauwan Tobing; Nidianti, Ersalina; Romdloni, Muhammad Afwan (Environmental and Toxicology Management, 2023)
Toxoplasmosis is a zoonotic disease caused by the parasite Toxoplasma gondii, which is transmitted through cats as definitive hosts and also infect poultry. This occurs because poultry ingest food contaminated with oocysts of Toxoplasma gondii. The most commonly consumed poultry are chicken and duck. This study aims to compare the counts of Toxoplasma gondii in chicken and duck brain samples sold at Keputran Market, Surabaya. This research is an analytical observational study with a cross-sectional approach, using direct preparation and flotation methods as research instruments. The samples in this study consisted of 24 chicken brain samples and 24 duck brain samples. The statistical analysis used was the Chi-Square test. The results showed that 16.7% (8 samples) of the chicken brain samples were positive and 33.3% (16 samples) were negative for Toxoplasma gondii. Meanwhile, 12.5% (6 samples) of the duck brain samples were positive and 37.5% (18 samples) were negative for Toxoplasma gondii. The data were analyzed using the Chi-Square test, resulting in a value of 0.752 (≥0.05), indicating that there is no significant difference in the presence of Toxoplasma gondii between the chicken and duck brain samples sold at Keputran Market, Surabaya.